2011
DOI: 10.1016/j.eswa.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Selection of new production facilities with the Group Analytic Hierarchy Process Ordering method

Abstract: a b s t r a c tThis paper presents the Group Analytic Hierarchy Process Ordering (GAHPO) method: a new multi-criteria decision aid (MCDA) method for ordering alternatives in a group decision. The backbone of the method is the Analytic Hierarchy Process (AHP) which is separated into two hierarchies for a cost and a benefit analysis. From these two analyses, a partial ordinal ranking can be deduced, where three relations between alternatives exist: the preference, indifference, and incomparability. A complete ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(57 citation statements)
references
References 56 publications
0
54
0
3
Order By: Relevance
“…Group decision making is becoming an increasingly important part of multiple criteria decision making (Ahmad, Saman, Mohamad, Mohamad, & Awang, 2014;De Brucker, Macharis, & Verbeke, 2013;Ishizaka & Labib, 2011a;Kuzman, Grošelj, Ayrilmis, & Zbasnik-Senegacnik, 2013;Ren, Fedele, Mason, Manzardo, & Scipioni, 2013;Skorupski, 2014;Wang, Peng, Zhang, & Chen, 2014;Yu & Lai, 2011). Multiple stakeholders can contribute a variety of experiences, expertise and perspectives, and a group can better deal with the complexity of the problem than a single decision maker (DM).…”
Section: Introductionmentioning
confidence: 99%
“…Group decision making is becoming an increasingly important part of multiple criteria decision making (Ahmad, Saman, Mohamad, Mohamad, & Awang, 2014;De Brucker, Macharis, & Verbeke, 2013;Ishizaka & Labib, 2011a;Kuzman, Grošelj, Ayrilmis, & Zbasnik-Senegacnik, 2013;Ren, Fedele, Mason, Manzardo, & Scipioni, 2013;Skorupski, 2014;Wang, Peng, Zhang, & Chen, 2014;Yu & Lai, 2011). Multiple stakeholders can contribute a variety of experiences, expertise and perspectives, and a group can better deal with the complexity of the problem than a single decision maker (DM).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is Ishizaka and Labib (2011b), who develop the Group Analytic Hierarchy Process Ordering (GAHPO) method. In this approach, the stakeholders are incorporated into a level of the hierarchy.…”
Section: Group Aggregationmentioning
confidence: 99%
“…Ishizaka and Labib presented the group analytic hierarchy process ordering method: a new multi-criteria decision aid method for ordering alternatives in a group decision. Authors found four main advantages: significant reduction of time and effort in the decision process; easiness for the decision makers to arrive at a consensus; enhancement of the decision quality and documentation with justification of the decision made [12]. However, AHP is frequently criticized for its inability to adequately accommodate the inherent uncertainty and imprecision associated with mapping decision maker perceptions to extract number.…”
Section: Review Of Literaturementioning
confidence: 99%